A Comprehensive Analysis of Hydrogen–Gasoline Blends in SI Engine Performance and Emissions - Zdeslav Jurić; Tino Vidović; Jakov Šimunović; Gojmir Radica (Energies, 2024)
This study investigates the influence of adding hydrogen as an additive to gasoline in a four-stroke engine, utilizing comprehensive thermodynamic comparative analysis conducted with self-developed engine model. This research aims to assess the performance, emissions, and efficiency of the engine when using gasoline–hydrogen blends, and to provide insights into the potential benefits of this approach. First, the engine performance and emissions under different hydrogen blending levels were examined. A range of different air/fuel ratios (rich to lean) and varying percentages of hydrogen were considered. This systematic variation allowed for a detailed evaluation of the influence of hydrogen content on combustion efficiency, power output, and emissions characteristics. The analysis results included key parameters such as indicated specific fuel consumption and mean effective pressure. Additionally, the study focused on the range prediction of nitrogen oxide (NOx) emissions, which are a critical environmental concern associated with internal combustion engines. The analysis of pressure and temperature profiles throughout the engine cycle shed light on the combustion characteristics and efficiency improvements associated with hydrogen addition. In terms of emissions, the study projected that all emissions were reduced except NOx, which is highly dependent on hydrogen percentage, and might be reduced in some cases, but with the higher temperatures and pressures associated with hydrogen addition, in most cases, there is actually a NOx increase, especially at higher engine loads.